A new method for traumatic renal injury in a canine model. Issue 3 (March 2017) - Cao, Zhi‐Qiang; Liang, Ming; Li, Shawn Xiang; Li, Xin; Han, Yaling
Abstract : Background : Selective transcatheter angiographic embolization (TAE) is an important method for efficient and accurate hemostasis in organ injuries during emergency settings. Sometimes, TAE cannot be performed on patients because of the limitations imposed by their condition. Methods : A total of 32 canines with traumatic right renal wounds were prepared by stab injuries. The canines were randomly divided into four groups according to different treatments. Group A was the renal neoplasty group ( n = 8). Group B was the TAE group ( n = 8). Group C was the group with temporary transcatheter bung associated with the renal neoplasty (TTBR) ( n = 8), and Group D was the sham surgery control group ( n = 8). Clinical trauma database, outcomes, and complications were analyzed to determine the feasibility and efficacy of different methods. Results : All canines were rescued in a timely manner. There was gross hematuria in six canines (18.8%). Only one (3.1%) animal died during follow‐up because of uremia. The complication rate was not statistically different according to management type (Groups A, B, and C vs. Group D; p = 0.332, p = 0.372, and p = 0.345, respectively). Groups B and C did better in protecting the damaged renal function with respect to creatinine than Groups A and D ( p = 0.013 and p = 0.032, respectively). However, Group C did a better job in protecting the damaged renal function than Group B ( p = 0.015). Conclusion : Use of TTBR can protect the damaged organ's functions more efficiently. Combined with the hybrid operating shelter, the method is a good damage control method for treating similar trauma in emergencies.